(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Terminology translation is a specialty within the broader field of translation that focuses on accurately and accurately conveying terminology from one language to another. In this article, we discuss the different types of compliance in terminology translation, what they mean and the strategies used to achieve them.